1997
DOI: 10.1007/s002770050344
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin and erythropoietin activate inside-out signaling of integrin and enhance adhesion to immobilized fibronectin in human growth-factor-dependent hematopoietic cells

Abstract: Erythropoietin (EPO) and thrombopoietin (c-MPL ligand; TPO) are structurally similar cytokines and support respectively, the proliferation and differentiation for erythroid and megakaryocytic lineages, as well as more primitive progenitors. We studied the effect of these cytokines on the induction of adhesion of human growth-factor-dependent hematopoietic cells to immobilized fibronectin, which is a main component of the extracellular matrix in the bone marrow. MO7ER cells that are genetically engineered to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Carboxypeptidase (MAX.1) J04970 ‫18.5מ‬ <0.0001 1.0000 1.0000 MAX.1 associated with monocyte to macrophage differentiation and is expressed in AML cells (Rehli et al 1995 (Bundgaard et al 1994), NGAL specific granules are marker for neutrophil maturation (Le Cabec et al 1997). Beta 1 integrin D U33880 ‫21.5מ‬ 0.0021 1.0000 1.0000 TPO up-regulates adhesion of hematopoetic progenitors to fibronectin through activation of integrin alpha4beta1 and alpha5beta1 (Gotoh et al 1997). Sp4 transcription factor X68561 ‫60.5מ‬ 0.0030 1.0000 1.0000 Sp4 not well characterized but closely related to Sp1 (Suske 1999), TPO activates several Sp1-dependent genes during megakaryopoiesis (Wang et al 1999 (Streit et al 1999), close relative thrombospondin 1 is negative regulator of megakaryopoiesis (Chen et al 1997;Touhami et al 1997 (Marlton et al 1995;Mancini et al 2000), CML/ALL translocations identified in 10q (Kagan et al 1989;Aguiar et al 1997;Salvati et al 1999 (Melnick et al 1999), isochromosomes on 17q common (Fioretos et al 1999) Biglycan J04599 ‫71.4מ‬ 0.2119 1.0000 1.0000 Xq28 Translocation found in AML (Weis et al 1985), common in ALL (Stern 1996 Dataset from Golub et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Carboxypeptidase (MAX.1) J04970 ‫18.5מ‬ <0.0001 1.0000 1.0000 MAX.1 associated with monocyte to macrophage differentiation and is expressed in AML cells (Rehli et al 1995 (Bundgaard et al 1994), NGAL specific granules are marker for neutrophil maturation (Le Cabec et al 1997). Beta 1 integrin D U33880 ‫21.5מ‬ 0.0021 1.0000 1.0000 TPO up-regulates adhesion of hematopoetic progenitors to fibronectin through activation of integrin alpha4beta1 and alpha5beta1 (Gotoh et al 1997). Sp4 transcription factor X68561 ‫60.5מ‬ 0.0030 1.0000 1.0000 Sp4 not well characterized but closely related to Sp1 (Suske 1999), TPO activates several Sp1-dependent genes during megakaryopoiesis (Wang et al 1999 (Streit et al 1999), close relative thrombospondin 1 is negative regulator of megakaryopoiesis (Chen et al 1997;Touhami et al 1997 (Marlton et al 1995;Mancini et al 2000), CML/ALL translocations identified in 10q (Kagan et al 1989;Aguiar et al 1997;Salvati et al 1999 (Melnick et al 1999), isochromosomes on 17q common (Fioretos et al 1999) Biglycan J04599 ‫71.4מ‬ 0.2119 1.0000 1.0000 Xq28 Translocation found in AML (Weis et al 1985), common in ALL (Stern 1996 Dataset from Golub et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…In combination with Flt3͞Flk2 ligand, TPO has been reported to support the expansion of human umbilical cord blood HSC up to 2 ϫ 10 5 -fold (31). In addition, TPO modifies the expression of adhesion receptors on HSC and cell lines, inducing adhesion to stroma and extracellular matrix (32,33). Finally, long-term repopulating HSC express c-mpl (34).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, phagocytosis of IgG-opsonized particles can be inhibited by small interfering RNA reduction of either DOCK180 or CrkII, which is the predominant Crk isoform in macrophages [48]. Since Syk can also phosphorylate Vav [50] and associate with several adaptor molecules such as Crk [51], it is possible that the ITAM recruited Syk may also activate GEFs, dependent or independent of SFKs.…”
Section: Introductionmentioning
confidence: 99%